Ultra-Precision Replication Technology for Fabricating Spiral-Structure Metamaterial - Zhang, Weiguo; Zhu, Guodong; Zhu, Xiaoqiang; Du, Chunlei (Frontiers in Physics, 2020)
Spiral-structure metamaterial (SSM) is of great importance, however, there are fewer methods to fabricate SSM due to limitations of material particularity and working accuracy. In this paper, a systematic scheme for fabricating SSM is proposed by employing the metal mold making with diamond-based ultra-precision turning technique and then molding replication method. By studying the path planning algorithm of the turning, molding error law, and a technique of how to compensate for the error, a solution for SSM is consequently formed. Our experimental results show a satisfying SSM with a surface roughness under 5 nm and a surface shape error under 0.63% of the designed wavelength (30 um). Moreover, this SMM element is processed within 10 min, with low cost materials and processes. Based on these advantages, our SSM processing scheme shows a remarkable potential in precise fabricating phase plates and industrialized application of terahertz metamaterial in the future.